(untitled) (Tanzania Medical Journal, 2009)
Toxoplasmic encephalitis is a common opportunistic infection in HIV infected individuals in sub-Saharan Africa but is difficult to treat in settings where first line therapy is not available. Fansidar has been recommended as an alternative regimen in these settings. In this report we describe the case of a patient with toxoplasmic encephalitis who was treated with fansidar with good response but fatal side effects. This case illustrates the potential dangers oftreating toxoplasmic encephalitis with fansidar. Accordingly, we alsoreview the literature regarding alternative treatment regimens fortoxoplasmic encephalitis that may be equally effective but less toxicthan fansidar.Keywords: toxoplasmic encephalitis, fansidar,pancytopenia, hyperpigmentation